Real Time System for Vehicle Scheduling, Tracking and Monitoring and Analysis - T, Swetha Reddy; K, Venkateswara Rao; Satri, Pullanna (International Journal of Computer Sciences and Engineering, 2019)
An advanced vehicle scheduling, monitoring and tracking system is to be designed and implemented for booking and monitoring the vehicles from one location to other location in real time and provide safety environment to the traveller. The proposed system has to use GPS/GPRS/GSM Modules which includes all the three things namely GPS GPRS GSM. The GPS provides current location of the vehicle; GPRS sends the tracking information to the server and the GSM is used for sending alert message to vehicle allotted person mobile. The booking of vehicle is done through priority scheduling algorithm The proposed system would place inside the vehicle whose position is to be determined on the web page and monitored in real time. The system will compare the current trajectory of the vehicle with the predefined path specified. If any deviation is observed, it will send an alert message to the related person. The cost analysis is done and cost is estimated based on the distance travelled.